PENGOLAHAN DAUN LAMTORO SECARA FISIK DENGAN BENTUK MASH, PELLET DAN WAFER TERHADAP PERFORMA DOMBA (Physics processing of leucaena leaves by mash, pellet and wafer on the performance of sheep) - Dipa Argadyasto; Yuli Retnani; Didid Diapari (Buletin Ilmu Makanan Ternak, 2015)
Leucaena leaves are an alternative forage of protein source for ruminants containing mimosineas anti-nutrition. Leucaena leaves processing necessary to reduce the content of mimosine, such as physical processing in the form of mash, pellets and wafers. This experiment was designed by randomized block design with 4 levels of treatment and 3 blocks of sheep body weight. The levels of treatment were R1 : control diet, R2 : control diet + 15% leucaena leaves in mash, R3 : control diet + 15% leucaena leaves in pellet and R4 : control diet + 15% leucaena leaves in wafer. Based on the results, the form of pellet and wafer able to reduce mimosine content more than 30% compared to mash. The results showed values significantly different (P <0.05) on dry matter intake, organic matter, crude protein, body weight gain and IOFC. Treatment of R4 showed dry matter intake of 1062 g/head/day, this value is 16% greater than the R1. Body weight gain and IOFC from treatment R4 of 145.54 g/head/day this value is 102% greater than the R1.